From can see to can't : Texas cotton farmers on the southern prairies - Sitton, Thad, 1941- (University of Texas Press, 1997)
This book offers a view of Texas farming in the late 1920s. From breaking ground, to planting, cultivating and harvesting, to how the family lives, their houses, food and clothing.